Polyomavirus-Specific Cellular Immunity: From BK-Virus-Specific Cellular Immunity to BK-Virus-Associated Nephropathy? - Dekeyser, Manon; François, Hélène; Beaudreuil, Séverine; Durrbach, Antoine (Frontiers in Immunology, 2015)
In renal transplantation, BK-virus-associated nephropathy has emerged as a major complication, with a prevalence of 5–10% and graft loss in >50% of cases. BK-virus is a member of the Polyomavirus family and rarely induces apparent clinical disease in the general population. However, replication of polyomaviruses, associated with significant organ disease, is observed in patients with acquired immunosuppression, which suggests a critical role for virus-specific cellular immunity to control virus replication and prevent chronic disease. Monitoring of specific immunity combined with viral load could be used to individually assess the risk of viral reactivation and virus control. We review the current knowledge on BK-virus specific cellular immunity and, more specifically, in immunocompromised patients. In the future, immune-based therapies could allow us to treat and prevent BK-virus-associated nephropathy.